Nephrotoxicity Evaluation of Methanolic Extracts of Calliandra surinamensis Seeds in Rodents - Eze, Patricia Nnebuogo; Obielumani, Joy Ovigwe; Omoruyi, Uwaila; Ogbeide, Osahon Kennedy; Irabor, Emmanuel Enoguan Igodaro (Faculty of Natural and Applied Sciences Journal of Applied and Physical Sciences, 2025)
Calliandra surinamensis seed has been used historically in folk medicine for various purposes. However, its safety profile, particularly its potential nephrotoxic effects, remains unknown. This study aimed to investigate the nephrotoxic effects of the methanolic extract of Calliandra surinamensis seed on kidney functions, along with histopathology assessment of the kidneys. Acute toxicity and sub-chronic toxicity methods were conducted in Wistar rats using modified Lörks’ method, following the Organization of Economic Cooperation and Development (OECD) guidelines, with testing chemicals 423 and 407 to determine the nephrotoxic effects of the seed. The mean Lethal Dose (LD50) could not be determined as there was no mortality. The kidney function parameters indicated an increase in the serum urea in the group treated with 400 mg/kg and 800 mg/kg of the extract, with mean values of 25.58 and 29.54, respectively, suggesting reduced renal clearance or increased protein catabolism. The Creatinine levels remained relatively stable, despite a slight increase at 800 mg/kg (0.39). However, values across all groups are comparable, including the control (0.40), suggesting no glomerular filtration impairment, as creatinine is a more stable marker. There were disturbances in electrolyte balance with more pronounced effects at the highest dosage (800 mg/kg). The average organ weight of the group treated with the seed extract and the control showed statistically no significant difference (P>0.05). These findings highlight that the methanolic extract of Calliandra surinamensis seed did not exhibit any nephrotoxic effects in Wistar rats, particularly at higher doses. However, further histopathological assessment and urine analysis would be beneficial to confirm and elaborate on the kidney parameters.